2021
DOI: 10.3389/fped.2021.780518
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Developmental and Respiratory Outcomes Among Preterm Infants With Bronchopulmonary Dysplasia

Abstract: Objectives: To examine the importance of perinatal and postnatal environmental factors on developmental and respiratory outcomes among preterm infants with bronchopulmonary dysplasia (BPD).Methods: Preterm infants (<32 weeks of gestation) born at a single tertiary medical center between 2012 and 2015 were included. Development was assessed at 12 months corrected age. Parents retrospectively completed a health and lifestyle questionnaire reviewing their child's health during the first 2 years of life. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…These models navigate the intricate landscape of clinical and genetic risk factors to discern infants with BPD within research populations. Notable instances of artificial intelligence in BPD research are eloquently delineated in Table 1 [31][32][33][34][35]. Using machine learning, the authors built predictive models that incorporated clinical and genetic data (from identified risk genes).…”
Section: Machine Learning and Artificial Intelligence: Transforming M...mentioning
confidence: 99%
“…These models navigate the intricate landscape of clinical and genetic risk factors to discern infants with BPD within research populations. Notable instances of artificial intelligence in BPD research are eloquently delineated in Table 1 [31][32][33][34][35]. Using machine learning, the authors built predictive models that incorporated clinical and genetic data (from identified risk genes).…”
Section: Machine Learning and Artificial Intelligence: Transforming M...mentioning
confidence: 99%
“…Bronchopulmonary dysplasia (BPD) is a chronic lung disease of the premature newborn. It is characterised by abnormal lung development provoked by factors such as mechanical ventilation, oxygen therapy or poor nutrition (1,2) . Advances in the care of premature infants and the increased survival of the most immature ones have resulted in an increased incidence of BPD, which now affects about 50 % of those born with less than 30 weeks of gestational age, according to the Vermont Oxford Network (3,4) .…”
mentioning
confidence: 99%